Cotton LIM domain‐containing protein GhPLIM1 is specifically expressed in anthers and participates in modulating F‐actin. (7th October 2014) - Li, L.; Li, Y.; Wang, N.‐N.; Li, Y.; Lu, R.; Li, X.‐B.; Liu, B.
Abstract As one form of actin binding protein (ABP), LIM domain protein can trigger the formation of actin bundles during plant growth and development. In this study, a cDNA (designated GhPLIM1) encoding a LIM domain protein with 216 amino acid residues was identified from a cotton flower cDNA library. Quantitative RT‐PCR indicated that GhPLIM1 is specifically expressed in cotton anthers, and its expression levels are regulated during anther development of cotton. GhPLIM1:eGFP transformed cotton cells display a distributed network of eGFP fluorescence, suggesting that GhPLIM1 protein is mainly localised to the cell cytoskeleton. In vitro high‐speed co‐sedimentation and low co‐sedimentation assays indicate that GhPLIM1 protein not only directly binds actin filaments but also bundles F‐actin. Further biochemical experiments verified that GhPLIM1 protein can protect F‐actin against depolymerisation by Lat B. Thus, our data demonstrate that GhPLIM1 functions as an actin binding protein (ABP) in modulating actin filaments in vitro, suggesting that GhPLIM1 may be involved in regulating the actin cytoskeleton required for pollen development in cotton.